Penguatan Layanan Medis dan Gizi Masyarakat Terdampak Bencana melalui Penyediaan Obat-Obatan Esensial di Desa Pahlawan, Kabupaten Aceh Tamiang - Zuleha Zuleha; Radhali Radhali; Melfy Wulandari; Farah Saghira Dhani; Ine Andriani (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
The flash flood disaster that struck Pahlawan Village, Aceh Tamiang Regency, disrupted community access to health and nutrition services. The limited availability of essential medicines and the increased risk of post-disaster diseases required rapid and structured intervention. This activity aimed to strengthen medical and nutritional services for disaster-affected communities through the provision of essential medicines, field health services, and nutritional interventions in Pahlawan Village. The activity was carried out for 14 days post-disaster using a direct approach, which included the establishment of mobile health posts, distribution of essential medicine packages, nutritional screening for toddlers and pregnant women, provision of ready-to-eat meals and micronutrient supplements, and community health education. The provision of essential medicines combined with medical services and nutritional interventions effectively reduced morbidity rates and prevented the worsening of nutritional status among disaster-affected communities. The main challenges are program sustainability and the strengthening of referral systems. Collaboration between the village government, local health center (Puskesmas), and local volunteers is the key to long-term success.